Handsigns : a sign language alphabet - Fain, Kathleen (San Francisco : Chronicle Books, 1993)
Presents an animal for each letter of the alphabet, accompanied by the corresponding sign for that letter in American Sign Language.
Publisher's Weekly
School Library Journal
Horn Book Magazine
6.2
RL 1, ages 4-7 (cover)
Keywords: American Sign Language -- Alphabet -- Juvenile literature; Sign language; Alphabet; Animals; Sign language; Alphabet; Animals